Industrial and Environmental Democracies as Models of a Politically Organized Relationship Between Society and Nature - St’ahel, Richard (Studia Philosophiae Christianae, 2023)
This paper is based on the concept of environmental political philosophy and from its perspective, it highlights the weaknesses and contradictions of contemporary, existing democracies. It aims to formulate an outline of the concept of environmental democracy, following the accounts of M. Bookchin, R. Morrison and H. Skolimowski, as well as international environmental law enshrined in United Nations documents and resolutions. It is based on the hypothesis that the preservation of a democratic political system in a situation of a collapsing planetary system (the Anthropocene) requires improving the foundations of democratic theory with the insights of the Earth system sciences, particularly of political ecology and critical environmentalism. Through philosophical analysis, explanation and interpretation, this paper explores an environmental democracy that would, on the one hand, preserve the basic constitutional principles of current democratic constitutional regimes, and, on the other hand, reconcile them with the current state of understanding in the Earth sciences concerning the vulnerability of the planetary system. In a sense, J. Habermas’s understanding of human rights characterizes the concept of environmental democracy as a realistic utopia. The author concludes by drawing up the imperative of sustainability, which he sees as a guiding organizing principle of institutions and public policies for the climatic, demographic and economic regime of the Anthropocene. -------------------------- Received: 16/12/2022. Reviewed: 09/03/2023. Accepted: 30/03/2023.